GUIDE: a randomised non-comparative phase II trial of biomarker-driven intermittent docetaxel versus standard-of-care docetaxel in metastatic castration-resistant prostate cancer (clinical trial protocol). (April 2022) - Conduit, Ciara; Mak, Blossom; Qu, Wenjia; Lulio, Juliana Di; Burder, Ronan; Bressel, Matthias; Cusick, Thomas; Dhillon, Haryana M.; Lourenço, Richard De Abreu; Underhill, Craig; Torres, Javier; Crumbaker, Megan; et al.
Objective: To determine the efficacy and safety of intermittent docetaxel chemotherapy guided by circulating methylated glutathione S-transferase Pi-1 ( mGSTP1 ) in men with metastatic castration-resistant prostate cancer (CRPC). Patients and Methods: GUIDE (NCT04918810) is a randomised, two-arm, non-comparative phase-2 trial recruiting 120 patients at six Australian centres. Patients with Prostate Cancer Working Group-3 defined metastatic CRPC who are commencing docetaxel 75 mg/m 2 q3w will be pre-screened for detectable mGSTP1 at baseline ± following two cycles of treatment. Those with detectable plasma mGSTP1 at baseline that becomes undetectable after two cycles of chemotherapy will be eligible for GUIDE. Prior to Cycle 4 of docetaxel, these patients are randomised 2:1 to one of two treatment arms: Arm A (cease docetaxel and reinstitute if mGSTP1 becomes detectable) or Arm B (continue docetaxel 75 mg/m 2 q3w in accordance with clinician's usual practice). The primary endpoint is radiographic progression-free survival. Secondary endpoints include time on treatment holidays, safety, patient-reported outcomes, overall survival, health resource use, and cost associated with treatment. Enrolment commenced November 2021. Results and Conclusion: The results of this trial will generate data on the clinical utility of mGSTP1 as a novel biomarker to guide treatment de-escalation in metastatic CRPC.